Faktor–Faktor Yang Mempengaruhi Output Pertanian Tanaman Pangan di Indonesia - Rafi Hidayat; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to systematize and explain the effect of land area, fertilizer use and labor on agriculture output of food crops in Indonesia. This type of research is quantitative research, the data used is secondary data which is analyzed using panel regression analysis. The estimation result show that land area has a negative and insignificant effect on agricultural output of food crops in Indonesia, the amount of fertilizer use has a positive and significant effect on agricultural output of food crops in Indonesia and labor has a negative and insignificant effect on agricultural output of food crops in Indonesia. Therefore this study proposes the government to be able to run a program that can increase land production power and labor production power in order to increase agricultural output of food crops.